Sifat Fisik, Kandungan Vitamin C dan Total Padatan Buah Pandan Tikar (Pandanus tectorius Park.) pada Tiga Tingkat Kematangan - Devila Maker; Zita Letviany Sarungallo; Budi Santoso; Rossa Martha Marlen Latumahina; Cicilia Maria Erna Susanti; Nurhaidah Iriyani Sinaga; Diana Nurini Irbayanti (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2018)
Pandan tikar (Pandanus tectorius Park.) fruit has the potential to be processed into various food products nevertheless the information on the right maturity level to be processed is limited. This study aims to determine the performance of pandan tikar fruit based on physical properties, vitamin C and total soluble solids (TSS) content at three levels of maturity. The fruits were collected from tress that grown at Mansinam Island and costal area of Northern Manokwari. Observations were made to changes in fruit performance, including the shape, color, weight and size of the fruit drupa, the content of vitamin C as well as TSS in three maturity levels (semi-ripe, ripe and over-ripe). The results of this study indicate that the fruit shape of pandan tikar was oval and continue to develop in weight, width and length of whole fruit and part of fruit (drupa and pith) during maturity development. The color of semi-ripe phase was light yellow then change to yellow in ripe phase and dark yellow in over-ripe phase. The highest vitamin C content was obtained on pandan tikar fruit from costal area of Northern Manokwari, and the maximum of Vitamin C content found in the mature phase (138.3 mg/100 g), and then decreased in over-ripe phase (49.5 mg/100 g). The TSS were obtained on pandan tikar fruit from Mansinam Island, and will increase from 5.2 to 12.5 °Brix with increasing fruit maturity level. The maximum Vitamin C and TSS of pandan tikar fruit found in the ripe and over-ripe phase; therefore the fruit in the phase is good for producting jam, dodol and syrup.